Socio-ecological vulnerability to climate change/variability in central rift valley, Ethiopia - Mekonnen, Z.; Woldeamanuel, T.; Kassa, H. (Elsevier, 2019)
Climate change/variability and environmental degradation have increased in the central rift valley of Ethiopia, which in turn making the people inhabiting in that ecosystem more vulnerable to the impacts. The purposes of this study were to assess the vulnerability of households and agro-ecosystems to climate change and environmental degradation and the factors determining vulnerabilities in the central rift valley, Ethiopia. Data were collected between November 2014 and May 2015 by interviewing 355 respondents. This has been supplemented with focus group discussions and key informant interviews. The indicator and matrix methods were used to describe socio-ecological vulnerabilities. The results showed that about 9% of the respondents were highly vulnerable to climate change/variability, and environmental degradation. Households in the lowland have the largest proportion of high vulnerable households (60%), while households in highland have the largest proportion of low vulnerable households (30%). In the lowland agro-ecology, the adaptive capacity component has contributed the largest share to household's vulnerability index to the impacts of climate change/variability and environmental degradation. The sensitivity component has higer contribution in highland agro-ecology and the exposure component in the midland agro-ecology. There were variations of income deviation between agro-ecologies that lead to variation in vulnerability of households. Household vulnerability index has shown a very light negative correlation with livelihood diversification index. The poorest households with little share of the total income distribution and with low livelihood diversity index, were the most vulnerable. The results showed that the highest exposure index on ecosystem functions and agricultural performance were in the lowland agro-ecology. This study highlighted the need to assess the social and ecological vulnerabilities in integrated approach as singling out one from the other is difficult. That is, social vulnerability impacts ecological vulnerability and vice versa.